2000
DOI: 10.21236/ada393834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alkyd Primers

Abstract: In October 1999, General Eric K. Shinseki, Chief of Staff of the Army (CSA), announced the establishment of an interim force, known as the Interim Brigade Combat Team (IBCT), to fill a perceived void in force capability and strategic responsiveness. The expectation of the IBCT is that it is totally air deployable anywhere in the world within 96-hours of the first aircraft taking off. The IBCT Operations and Organization (O&O) design postulates the IBCT to employ immediately upon arrival. This is accomplished u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, another relevant mediator is the platelet-activating factor (PAF). Recent studies have shown that the epithelial/endothelial cells of the target organs are actively involved in the recruitment and activation of inflammatory cascades in allergic diseases (50). These endothelial cells promote the expression of vascular cell adhesion molecules and Eselectin, which increase the adhesion of circulating leukocytes to the endothelial cells.…”
Section: Phases Of the Allergic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…However, another relevant mediator is the platelet-activating factor (PAF). Recent studies have shown that the epithelial/endothelial cells of the target organs are actively involved in the recruitment and activation of inflammatory cascades in allergic diseases (50). These endothelial cells promote the expression of vascular cell adhesion molecules and Eselectin, which increase the adhesion of circulating leukocytes to the endothelial cells.…”
Section: Phases Of the Allergic Responsementioning
confidence: 99%
“…The relative advantages of antihistareines were initially based on their ability to competitively inhibit the Hi-receptor binding of histamine (50). However, at the appropriate doses many antihistamines inhibited histamine release from mast cells and perhaps mast-cell activation itself (21).…”
Section: Antihistamines In the Treatment Of Auergic Rhinitismentioning
confidence: 99%